RANCANGAN PENGEMBANGAN SEKOLAH BERDASARKAN 8 STANDAR NASIONAL PENDIDIKAN SD N 6 DANGER - Fadma Rosita (LPPM Institut Pendidikan Nusantara Global, 2020)
ABSTRACT This research is a research on school development design based on 8 National Education Standards. The problems examined in this study are about the gaps in SD N 6 Danger and what programs will be carried out after the school development design is carried out. The purpose of this research is that schools can design or plan school development based on 8 SNPs. In addition, the goal to be achieved is for schools to determine programs to develop schools. The method used is descriptive qualitative research with the research subject is SD N 6 Danger. Data collection techniques are interviews, observation and documentation. The result of the research is that there are gaps in schools including the standard of facilities and infrastructure, and also from the standard of financing. The programs to be implemented are training programs for teachers, making printed books and educational aids (APE), and making requests for assistance from the central government.